Stature approximation of Malays, Chinese and Indian in Malaysia using radiographs of Femur, Tibia and Fibula - Amal Hayati Zainal Abidin,; Khairul Osman,; Sri Pawita Albakri Amir Hamzah,; Noor Hazfalinda Hamzah,; Ab Halim Mansar,; Normaizatul Afizah Ismail, (Penerbit UKM, 2011)
The study was conducted to create specific formulae for stature estimation of adult male population in Malaysia based on measurements of femur, tibia and fibula lengths using radiographic method. A number of thirty two Malaysians from hospitals involved as subjects in this study. The subjects were Malays (14), Chinese (8) and Indians (10) from 25-45 years old. The standing height of the subject was recorded before femur, tibia and fibula were scanned with an x-ray machine. The bones length was measured on the x-ray film in centimetres (cm) and analysed using Statistical Package for Social Sciences (SPSS) version 19.0 for Windows. The results showed a significant relationship (p < 0.05) between stature and measurements of length of femur, tibia and fibula. Stature of Malays and Indians were significant (p < 0.05) with measurements of length of femur, tibia and fibula but insignificant in Chinese. Simple Linear Regression Analysis was used to derive regression equation for single bone and Multiple Linear Regression Analysis was used to derive regression equation for combination of femur, tibia and fibula. Six formulae for stature estimation of adult male population in Malaysia were derived. The formulae consist of three formulae for single bone, a formulae for combination bones with unknown race, a formulae for combination bones of Malays population and a formulae for combination bones of Indians population. Formulae for combination bones had the highest correlation coefficient compared to the formula using a single bone. Standard error was found to be high in all the formulae due to small sample size. Extension for this study is essential to provide Malaysia with accurate formulae.